Mapping knowledge structure and research trends of knee osteoarthritis with meniscus in two decades: A bibliometric analysis - Chen, Weijian; Yang, Yaqin; Tang, Gangjian (Frontiers in Surgery, 2022)
Background: Knee osteoarthritis (KOA) is a chronic degenerative disease that is closely related to the meniscus. Currently, no bibliometric studies have jointly analyzed KOA and the meniscus. This study aimed to provide a comprehensive analysis of the knowledge structure of KOA and the meniscus across two decades and to identify the emerging research trends from a bibliometric perspective. Methods: All articles reporting KOA and the meniscus from 2001 to 2021 were obtained from the Web of Science Core Collection. R software, CiteSpace, Vos Viewer, and Microsoft Excel were used to analyze the publications including the authors, cited authors, journals, cited journals, country of research, institutions, and research focus. These data were used to generate visual knowledge maps of the outputs. Results: A total of 3,218 articles were retrieved. Guermazi was identified as the author who had contributed the most to the field and Osteoarthritis and Cartilage was identified as the most productive research journal. The United States is the global leader in the field and the center for international cooperation with less international collaboration occurring in Eastern Asia. Boston University was the most prolific institution. According to the data, ‘articular-cartilage’, ‘meniscectomy’, ‘follow-up’, ‘anterior cruciate ligament’ and ‘cartilage’ were identified as research hotspots in the field. ‘Consequences’, ‘prognostic-factors’, and ‘receptor’ were predicted as future hot topics of research. Conclusions: This study is the first comprehensive bibliometric study to jointly analyze KOA and the meniscus. Our data enable a better understanding of research trends and identified research hotspots and gaps in knowledge across the field. Our findings provide practical information for researchers to better understand the key research areas and identify the research frontiers and future hot topics.